The Effect of Organization Capital on the Cost of Bank Loans - Danielova, Anna; Francis, Bill B.; Teng, Haimeng; Wu, Qiang (Journal of Financial and Quantitative Analysis, 2023)
Abstract We find that organization capital is negatively related to the cost of bank loans. This finding is robust to additional analyses including those that address omitted variable bias and reverse causality. In addition, we find that organization capital reduces all-in-spread-undrawn. When we decompose the bank loan cost, we find that organization capital increases facility fees due to its risk-engendering characteristics. Finally, we find that organization capital is positively associated with a high likelihood of the presence of inventors and innovation output, consistent with the argument that organization capital is embedded in the key talent within a firm.